One feta in the grave - Kashian, Tina (Kashian, Tina. Kebab Kitchen mystery., 2019)
With a sand castle contest and live music, Ocean Crest bids a bittersweet farewell to tourist season. Summer will return next year <U+2026> but Archie Kincaid won<U+2019>t. The full-of-himself store owner has been fatally shot, soon after a screaming match with Lucy<U+2019>s best friend. Katie<U+2019>s far from the only suspect, though, since Archie had some bitter rivals<U+2014>as well as some relationships no one knew about. It<U+2019>s up to Lucy to look into some seedy characters and solve the case before the wrong person gets skewered <U+2026>